2015
DOI: 10.1642/auk-14-71.1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical montane birds have increased nesting success on small river islands

Abstract: Predation is the most important cause of nest failure in birds, and variation in predation risk has been associated with changes in nesting behaviors such as nest-site selection. Some birds choose favorable breeding sites on oceanic or large lake islands to increase their nesting success, but we do not know whether river islands with smaller water barriers provide similar “safe” conditions that decrease predation risk. We tested this in tropical birds by comparing daily survival rates (DSR; i.e. the probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The island can provide isolation from avian nest predators (i.e. snakes and mammals), reducing the risk of predation (Fontaine and Martin 2006 ; Ocampo and Londoňo 2015 ). In addition, human beings as well as predation were main causes of nest failure in a population of Central Finland (Leinonen 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…The island can provide isolation from avian nest predators (i.e. snakes and mammals), reducing the risk of predation (Fontaine and Martin 2006 ; Ocampo and Londoňo 2015 ). In addition, human beings as well as predation were main causes of nest failure in a population of Central Finland (Leinonen 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, foxes have been shown to impart strong control over seabird colonies [ 54 ], and increases in gull and Bald Eagle populations are correlated with ongoing declines in skimmers and other colonial waterbirds breeding in Virginia, USA [ 55 ]. While nesting success for passerines is generally low in tropical forests [ 56 ], skimmers can benefit from nesting on river islands [ 57 ] and from multi-species defense provided by allies, including the Large-Billed Tern ( Phaetusa simplex ) and Yellow-Billed Tern ( Sterna superciliaris ) [ 29 ]. The latter two species co-occur across the entire Amazon basin, yet neither appears on the Pacific Coast.…”
Section: Discussionmentioning
confidence: 99%
“…Kauffman et al (1997) have shown that many species have developed adaptive strategies to inhabit riparian and in-stream habitats, while recovering from disturbances caused by hydrological extremes. Fluvial islands may act as natural habitats and refuge for both plant communities (Barnes, 1985;Cooperman and Brewer, 2005) and birds (Lokemoen and Woodward, 1992;Ocampo and Londoño, 2015).…”
Section: Function Of Fluvial Islandsmentioning
confidence: 99%